Functional vitamin B12 deficiency in phenylketonuria patients and healthy controls: An evaluation with combined indicator of vitamin B12 status as a biochemical index. (July 2020) - Akış, Merve; Kant, Melis; Işık, İshak; Kısa, Pelin Teke; Köse, Engin; Arslan, Nur; İşlekel, Hüray
Background: Vitamin B12 deficiency frequently appears in phenylketonuria patients having a diet poor in natural protein. The aims of this study were to evaluate vitamin B12 status in phenylketonuria patients by using combined indicator of vitamin B12 status (cB12) as well as methylmalonic acid and homocysteine, more specific and sensitive markers, in comparison with healthy controls. Methods: Fifty-three children and adolescents with phenylketonuria under dietary treatment and 30 healthy controls were assessed cross-sectionally. Serum vitamin B12 and folate concentrations were analysed by chemiluminescence immunoassay. Plasma methylmalonic acid and total homocysteine concentrations were measured by liquid chromatography-tandem mass spectrometry and liquid chromatography, respectively. cB12 was calculated by using a formula involving blood parameters. Results: Methylmalonic acid and folate concentrations in phenylketonuria group were higher compared with controls. Methylmalonic acid concentrations were high in 56.5% of the patients and 26.7% of the controls with normal vitamin B12 concentrations. Based on cB12, a significant difference within the normal values was detected between the groups. However, although 24.5% of phenylketonuria patients and 13.3% of controls had decreased vitamin B12 status according to cB12, there was no significant difference. Conclusion: Children and adolescents with phenylketonuria having a strict diet can be at risk of functional vitamin B12 deficiency. This deficiency can be accurately determined by measuring methylmalonic acid concentrations. Calculation of cB12 as a biochemical index did not provide additional information compared with the measurement of methylmalonic acid alone, but may be helpful for classification of some patients with increased methylmalonic acid as having adequate vitamin B12 status.